Public debt and income inequality in times of austerity: dynamic panel evidence - Okeke, Angela; Alexiou, Constantinos (Taylor & Francis, 2025)
This paper examines the relationship between public debt levels and income inequality during periods of fiscal consolidation (austerity). Specifically, it investigates two key questions: (a) whether high public debt during fiscal adjustments exacerbates income inequality, and (b) whether the composition of these adjustments influences the debt–inequality link. To address these issues, we apply a panel threshold methodology using annual data from 16 OECD countries over the period 1980–2019. Our findings reveal that public debt significantly affects income inequality, with the impact intensifying during fiscal adjustments, particularly at moderate debt thresholds (30–60%). Furthermore, when comparing the effects of tax-based versus spending-based adjustments, the evidence shows that tax-based consolidations tend to produce more persistent negative effects on income inequality.
Keywords: 38 Economics; 3801 Applied Economics; 3802 Econometrics; 44 Human Society; 1.2 Psychological and socioeconomic processes; 10 Reduced Inequalities; 3801 Applied economics; 4404 Development studies; Austerity; dynamic threshold model; income inequality; public debt